2004
DOI: 10.3168/jds.s0022-0302(04)73293-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Feeding Space on the Inter-Cow Distance, Aggression, and Feeding Behavior of Free-Stall Housed Lactating Dairy Cows

Abstract: The objectives of this study were to determine whether doubling the amount of feeding space from 0.5 to 1.0 m per cow leads to increased spacing between cows at the feeder, fewer aggressive social interactions among cows, and ultimately increased feeding activity. Twenty-four lactating Holstein cows were provided with 0.5 and 1.0 m of feeding space per cow in a 2 x 2 crossover design replicated over time. Time-lapse video was used to quantify the inter-cow distance and incidence of aggressive displacements at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
161
1
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 226 publications
(176 citation statements)
references
References 19 publications
12
161
1
2
Order By: Relevance
“…With a zero-orts feeding system, it is reasonable to believe there still may be sorting throughout the day (DeVries et al 2005;Hosseinkhani et al 2008). In situations of feed bunk competition, this may result in those subordinate animals with poor feed bunk access at peak feeding periods (DeVries et al 2004) having to wait to feed at later hours in the day after the feed has already been sorted, thus increasing their risk of consuming a ration that is not designed to meet their nutritional requirements (Hosseinkhani et al 2008).…”
Section: Calculations and Statistical Analysismentioning
confidence: 99%
“…With a zero-orts feeding system, it is reasonable to believe there still may be sorting throughout the day (DeVries et al 2005;Hosseinkhani et al 2008). In situations of feed bunk competition, this may result in those subordinate animals with poor feed bunk access at peak feeding periods (DeVries et al 2004) having to wait to feed at later hours in the day after the feed has already been sorted, thus increasing their risk of consuming a ration that is not designed to meet their nutritional requirements (Hosseinkhani et al 2008).…”
Section: Calculations and Statistical Analysismentioning
confidence: 99%
“…O consumo individual de suplemento tem sido estimado utilizando-se indicadores inorgânicos, como o lítio (Kahn, 1994), o itérbio (Earley et al, 1999) e mais recentemente, o óxido crômico e o dióxido de titânio (Kincheloe, 2004;Marcondes et al, 2006).…”
unclassified
“…Reducing the space available for cows to eat increases competition (Mentink and Cook 2006). For example, DeVries et al (2004) showed that doubling feeding space from 0.5 m to 1.0 m per cow reduced by half the number of aggressive interactions while feeding. This reduction in aggressive behaviour allowed cows to increase feeding activity by Fig.…”
Section: Physical Design Of the Feed Barriermentioning
confidence: 99%